Education and Training Programmes for Health Professionals' Competence in Virtual Consultations: A Scoping Review - Britt Holst Lisbjerg; Louise Meyer Wind Mathiesen; Bettan Bagger; Lene Lauge Berring; Ditte Høgsgaard; Heidi Myglegård Andersen; Stine Thestrup Hansen; Mai‐Britt Hägi‐Pedersen (Journal of Clinical Nursing, 2026)
ABSTRACT Aims To map and synthesize which education and training programmes are available for current and future health professionals' competence in virtual consultations, with a special focus on training elements and structure. Design Scoping review following the PRISMA‐ScR framework. Methods Studies describing structured education or training in synchronous virtual consultations were included. Data were charted and synthesised to map training modes, educational elements, and terminology. Data Sources MEDLINE, CINAHL and Scopus (September 2024; updated September 2025). Grey literature was also screened. Results Twenty‐one studies were included. Five training modes were identified: simulation with standardised participants, avatar simulation, peer simulation, in situ training and Objective Structured Clinical Examination. A 5‐stage curriculum framework emerged: pre‐assess, prepare, conduct, follow‐up and post‐assess, followed by a catalogue of 34 diverse educational elements. Sixteen different terms were used to describe virtual consultations. Conclusion Evidence demonstrates an increasing focus on virtual consultation training, and a descriptive framework for organising training emerged, however, no consensus exists regarding specific elements, curriculum structure, terminology, or outcome evaluation. Implications for the Profession and/or the Patient Care The identified framework may guide curriculum development and support competence building across health professions. Impact This review addresses the lack of an overview of how virtual consultation training is structured. It identifies 34 core educational elements and a 5‐stage framework. The findings support educators and clinicians implementing training in digital care. Reporting Method Reported in accordance with PRISMA‐ScR and EQUATOR guidelines. Patient or Public Contribution No patient or public contribution.